Algorithm for constructing and solving the equilibrium equation of three-dimensional elastic bodies (Acta Education, 2024)
Modern requirements for elements of three-dimensional spatial prismatic structures require a high level of accurate calculations when determining the strength of elements. Therefore, the calculation of problems in this area in three-dimensional space requires taking into account not only elastic deformation, but in many cases also plastic deformation.